2016
DOI: 10.1111/jvh.12645
|View full text |Cite
|
Sign up to set email alerts
|

Simeprevir, daclatasvir and sofosbuvir for hepatitis C virus‐infected patients with decompensated liver disease

Abstract: Summary Approximately three million individuals in the United States are chronically infected with hepatitis C virus (HCV). Chronic HCV infection may lead to the development of compensated as well as decompensated liver cirrhosis. The Phase II IMPACT study was conducted in HCV genotype 1‐ or 4‐infected cirrhotic patients with portal hypertension or decompensated liver disease and assessed for the first time the combination of the three direct‐acting antivirals simeprevir, daclatasvir and sofosbuvir. Treatment‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
3
21
0
1
Order By: Relevance
“…Based on our findings, a multi‐DAA regimen involving the use of 3 or more DAAs may not be required in the majority of cases of SIM/SOF failure especially in those with decompensated cirrhosis and dual DAA therapy with LDV/SOF could be considered a viable option. Although multi‐DAA regimens utilizing 3 or more DAAs may also be highly effective, limitations to this strategy exist in a real‐world setting related to high cost and decreased access …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our findings, a multi‐DAA regimen involving the use of 3 or more DAAs may not be required in the majority of cases of SIM/SOF failure especially in those with decompensated cirrhosis and dual DAA therapy with LDV/SOF could be considered a viable option. Although multi‐DAA regimens utilizing 3 or more DAAs may also be highly effective, limitations to this strategy exist in a real‐world setting related to high cost and decreased access …”
Section: Discussionmentioning
confidence: 99%
“…Although multi-DAA regimens utilizing 3 or more DAAs may also be highly effective, limitations to this strategy exist in a realworld setting related to high cost and decreased access. 24 MODI ET AL.…”
Section: Pre-and Post-liver Transplantationmentioning
confidence: 99%
“…With the recent advent of direct‐acting antivirals (DAAs), the American Association for the Study of Liver Disease (AASLD), the Infectious Disease Society of America (ISDA), and the European Association for the Study of the Liver (EASL) now have guidelines that recommend the use of all‐oral DAA regimens for decompensated HCV cirrhosis patients . In a recent study conducted by Lawitz et al, 100% of decompensated HCV cirrhosis patients achieved a sustained virological response (SVR). Furthermore, a large‐scale trial conducted by Charlton et al demonstrated decompensated that HCV cirrhosis patients with Child‐Pugh (CP) class B and class C achieved SVR rates greater than 85% with DAA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…There is an abundance of data on the clinical improvement of Dec‐HCV patients following HCV eradication. Overall, a sustained virological response (SVR) is associated with a median 2‐point reduction in MELD score, a lower incidence of decompensation over 12 months post‐SVR, and a 30% chance of delisting . In the European study coordinated by Belli et al., and involving 11 European centres, 38/142 treated patients were delisted .…”
Section: How To Deal With Direct‐acting Antiviral Treatment Failure Bmentioning
confidence: 99%
“…Overall, a sustained virological response (SVR) is associated with a median 2-point reduction in MELD score, a lower incidence of decompensation over 12 months post-SVR, and a 30% chance of delisting. [172][173][174][175][176][177][178] In the European study coordinated by Belli et al, and involving 11 European centres, 38/142 treated patients were delisted. 165 In the Italian ITACOPS study, viral eradication was associated with a better liver function in about half of 224 patients treated.…”
Section: Commentmentioning
confidence: 99%